“Razones que se asocian a la desercion de psicoprofilaxis al II essalud Tarapoto-2006” - Paima Del Águila, Lleraldo (2008)
He was conducted a descriptive research combining qualitative methodology and the quantitative, triangulizando different methods and techniques, in order to determine the reasons associated with the desertion of pregnant women's obstetrical Psychoprophylaxis in the Hospital ESSALUD U of Tarapoto. The sample was formed in the following way: 75 pregnant women (40 pregnant women who defected and 35 pregnant women who met the scheduled sessions), 15 pregnant women and/or immediate postpartum, the Coordinator responsible for obstetrical Psychoprophylaxis, Director of the Hospital, Chief of OB/GYN and head of the obstetrical Psychoprophylaxis who applied designed and previously validated data collection instruments. The results more important was found: •! • the stronger the dropout reason was work (45%), followed by inadequate hours (22.5%), diseases and complications (17.5%) and problems of the facilitators (15%), among which...